MENSTRUAL FUNCTION DISORDERS IN ADOLESCENT GIRLS WITH DYSPLASIA OF CONNECTIVE TISSUES - Shavazi Nargiz Nuralievna; Nurmukhamedova Dildora Ulugbek kizi (Galaxy International Interdisciplinary Research Journal, 2022)
The article shows the role of mothers' adverse pregnancy and birth in the formation of pathology of the reproductive system, for the girls with connective tissue dysplasia. The most significant risk factors were revealed: the threat of premature termination of pregnancy, preeclampsia, preterm, birth, and also basic phenotypic features of connective tissue dysplasia syndrome were determined. Menstrual function disorders in adolescent girls are characterized by early menarche, hypomenstrual syndrome, uterine bleeding of puberty.